The Operation of Internal Quality Assurance in Schools of the Nikhomphatthana School Group under the Rayong Primary Educational Service Area Office 1 - ผลทาเลิศ, กมลรัตน์; ประวัติรุ่งเรือง, ประเสริฐ; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to study the operations of internal quality assurance in educational institutions; 2) to compare the operations of internal quality assurance in educational institutions classified by position, school size, educational background, and work experience; and 3) to study the guidelines for developing the operations of internal quality assurance in the Nikhom Phatthana school group under the Rayong Primary Educational Service Area Office 1. The sample size was determined using the Krejcie and Morgan table (1970: 608). Stratified random sampling was employed using school size as the stratum, followed by simple random sampling, resulting in a sample of 194 participants comprising 19 school administrators and 175 teachers. The quantitative research instrument was a 5-level rating scale questionnaire with an overall reliability coefficient of 0.982. Additionally, qualitative data were collected through interviews with 5 purposively selected informants. The qualitative data were analyzed using content analysis and presented descriptively. The statistics used for quantitative data analysis included frequency, percentage, mean, standard deviation, t-test, and One-way ANOVA. Paired differences were tested using Scheffe's method.           The results of the research found that: 1) Overall, the internal quality assurance operations of Nikhom Phatthana school group under the Rayong Primary Educational Service Area Office 1 were rated at the highest level (x̄= 4.64, S.D. = 0.378). Regarding individual aspects, the preparation of self-assessment reports received the highest mean score (x̄= 4.72, S.D. = 0.387) followed by the establishment of educational standards (x̄= 4.68, S.D. = 0.409) and monitoring and implementation (x̄= 4.66, S.D. = 0.429). The implementation of the educational development plan received the lowest mean score (x̄= 4.57, S.D. = 0.479). 2) The comparison of the internal quality assurance operations classified by position revealed no significant differences overall, except for the monitoring and implementation aspect, which showed a statistically significant difference at the .05 level. When classified by the size of the educational institution, the overall operations differed significantly at the .001 level. Specifically, the establishment of educational standards, evaluation and inspection, monitoring and implementation, and the preparation of self-assessment reports showed statistically significant differences at the .001 level. Meanwhile, educational development planning and the implementation of the development plan showed significant differences at the .01 level. Furthermore, when classified by educational level and work experience, there were no statistically significant differences, either overall or in individual aspects. 3) The guidelines for developing internal quality assurance operations in these educational institutions include: emphasizing collaboration among administrators, teachers, and stakeholders; utilizing the PDCA cycle as a driving mechanism; and establishing challenging yet achievable goals. Additionally, information technology should be applied to database management, and personnel development should be conducted to ensure accurate knowledge and understanding.